RELATIONSHIP OF MOTHER WORK WITH EXCLUSIVE ASSEMBLING IN CITY VILLAGE GAPU DISTRICT OF KOTA JUANG REGENCY OF BIREUEN - Raudhati, Sri (JURNAL KESEHATAN ALMUSLIM, 2017)
Exclusive breastfeeding is breast milk given in the first 6 months of the newborn without any other complementary food. According to the results of basic health research in 2010 has reached 92.7%, the coverage of deliveries assisted by health workers 82.2%, coverage of neonatal visits 71,4%, often inappropriate feeding and unsafe so as to cause 1, 5 million babies die from improper feeding. Working moms often do not give exclusive breastfeeding because of maternity leave for only 3 months, causing a mother to always take the practical path to solve breastfeeding problems by breastfeeding the baby. Based on coverage of exclusive breastfeeding in infants aged 0-6 months by province of Aceh in 2010 was 49.6%. To know the relation of mother's job with Exclusive Breastfeeding in Cot Gapu Village, Kota Juang District, Bireuen District. The research design used is with the type of analytical research. Sampling using Total Population, ie all mothers who have babies aged 6 months to 2 years and sampling done door to door. After statistical analysis with pearson chi squere between mother's job and exclusive breastfeeding was obtained c2 count 0.188 ≤ c 2 table 3,841, so it can be concluded that there is no relation of mother's job to exclusive breastfeeding.